Pengaruh Likuiditas, Profitabilitas, Leverage, dan Aktivitas dalam Memprediksi Financial Distress pada Perusahaan Subsektor Retail Trade yang Terdaftar di BEI - Widya Susanti; Nurjanti Takarini (Ekonomis: Journal of Economics and Business, 2022)
The purpose of this study is to analyze how financial ratios can affect the prediction of financial distress or financial distress in retail trade sub-sector companies listed on the Indonesia Stock Exchange. In this study, liquidity is represented by the Current Ratio, profitability is proxied by the rate of return on assets (ROA). Leverage is represented by the Debt to Equity Ratio, and the activity ratio is represented by total asset turnover (TATO). The dependent variable used is financial distress with the Modified Altman Z-Score Model as an indicator. The research population is all retail trade sub-sector companies listed on the IDX in 2018-2020. Sampling using purposive sampling technique and obtained 25 companies that fit the criteria with a 3 year research period. Logistic regression analysis was used as a data analysis method. From the results of logistic regression analysis, it shows that liquidity and leverage indicators have a significant effect in estimating financial distress or financial distress of retail trade sub-sector companies. Meanwhile, indicators of profitability and activity cannot influence the forecast of financial distress in retail trade sub-sector companies.